2004
DOI: 10.1017/s135561770410310x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of remote and anterograde memory impairment and neural correlates in alcoholic Korsakoff syndrome

Abstract: Alcoholic Korsakoff's syndrome (KS) is marked by remote memory impairment together with characteristic profound anterograde memory deficits. Despite previous studies of memory processes in KS, questions remain regarding the nature and severity of these impairments and identification of brain systems that underlie these different memory impairments. This study examined remote and anterograde memory function in 5 KS patients in comparison with 8 patients with Alzheimer's disease (AD) and 24 normal control subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 66 publications
4
39
0
Order By: Relevance
“…In line with our expectations and ample evidence of episodic memory and executive functions deficits (e.g., Brion et al, 2014;Fama, Marsh, et al, 2004;Wester, Leenders, Egger, & Kessels, 2013), individuals with Korsakoff's syndrome showed poorer PM (23% and 45% hits on the low and high salient condition, respectively) than those with chronic alcoholism. In general, Korsakoff patients performed at a low level indicating a severe PM deficit, but importantly their performance significantly differed from zero.…”
Section: Discussionsupporting
confidence: 88%
“…In line with our expectations and ample evidence of episodic memory and executive functions deficits (e.g., Brion et al, 2014;Fama, Marsh, et al, 2004;Wester, Leenders, Egger, & Kessels, 2013), individuals with Korsakoff's syndrome showed poorer PM (23% and 45% hits on the low and high salient condition, respectively) than those with chronic alcoholism. In general, Korsakoff patients performed at a low level indicating a severe PM deficit, but importantly their performance significantly differed from zero.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, these findings were consistent with those in an earlier study (Kopelman, 1991), which showed that performance on executive tests could predict 68.5% of the variance in Korsakoff patients on autobiographical and remote memory tasks, compared with only 21% of variance predicted by performance on anterograde memory tests. Fama et al (2004) carried out a related study, examining the performance of five Korsakoff patients on a test of Famous Presidents. They also found that remote memory impairment was not correlated with the severity of anterograde memory impairment.…”
Section: Retrograde Amnesiamentioning
confidence: 99%
“…These KS patients were a subset of those examined in our earlier studies (Fama et al, 2004a;Shear et al, 1996;Sullivan and Marsh, 2003) and had Wechsler Memory Scale-Revised (Wechsler, 1987) scores ranging from 34 to 45 points below their respective National Adult Reading Test (NART) scores. These differences exceeded the 1.5 SD difference criteria to confirm the presence of anterograde amnesia (Oscar-Berman et al, 1993;Weiskrantz, 1985) (Table 1).…”
Section: Participantsmentioning
confidence: 99%
“…Memory deficits in KS also involve components of remote memory (Kopelman, 1995;Kopelman et al, 1999;Squire et al, 2001) possibly arising from damage to posterior cortical systems (Fama et al, 2004a). In contrast to explicit memory processes for which learning is assessed by conscious recall or recognition of specific information encountered previously, implicit memory processes are assessed by modification of responses by previously encountered stimuli, without necessarily having conscious knowledge of learning (Graf and Schacter, 1985;Tulving and Schacter, 1990;Verfaellie and Keane, 2002).…”
mentioning
confidence: 99%